Serum Lipid Concentrations Are Associated With Negative Mental Health Outcomes in Healthy Women Aged 35–49 Years - Yu, Jingjie; Zhang, Zhihui; Li, Chunjun; Zhang, Jiarui; Ding, Zengbo; Zhu, Weili; Wang, Qiang (Frontiers in Psychiatry, 2021)
Background: Although the relevant underlying biological mechanisms are still lacking, mental disorders have been closely associated with several metabolic abnormalities including high rates of obesity and metabolic syndrome especially in vulnerable populations. Therefore, the current study aims to examine how metabolic parameters increase the risk for developing mood disorders in individuals stratified by gender and age. Methods: In a routine physical examination, 319 healthy participants were recruited and assigned to 6 different groups according to age (young adults: 25-34Y, middle age: 35-49Y, and older age: 50-65Y) in both males and females. A linear regression and bivariate correlation analysis were used to analyze the relationship between mood health outcomes measured by the Kessler 10 Psychological Distress Scale (K10) and the metabolic function. Results: The results demonstrated that there was a significant association between K10 scores and metabolic parameters, including Body Mass Index (BMI), total-, LDL-cholesterol, and triglyceride. Furthermore, poor mental health (higher K10 scores) was observed in individuals with increased BMI, total-, LDL-cholesterol and triglyceride levels particularly in middle-aged women relative to other groups. Limitations: This is a cross-sectional study with a small sample size and lacks longitudinal follow-up evidence and preventive interventions and therefore could not provide the causal inference of metabolic pathophysiology on the increased sensitivity to mental disorders. Conclusions: The potential association suggests that targeting of the metabolic parameters might give us a better understanding of the underlying mechanisms of psychiatric diseases and provide preventive strategies and potential treatment for those with metabolic disturbances especially in middle-aged females.